Differentiated High Grade Follicular Thyroid Carcinoma: Diagnostic Experience of New Entity - A Rare Case Report - Govindasamy Revathi; V Sriram; Erli Amel Ivan; Gandhi Ramya (Journal of Medical Sciences and Health)
Differentiated high-grade thyroid carcinoma (DHGTC) is a recently classified invasive high-grade follicular derived carcinomas that retain the architectural and cytologic features of well-differentiated follicular cell carcinomas with high-grade features like increased mitotic count and tumor necrosis. The prevalence of DHGTC in follicular thyroid carcinoma was found to be 0.146 [CI = 0.101-0.205]. To the best of my knowledge, this is the second case report of this new entity according to the recent WHO classification of Endocrine and Neuroendocrine tumours (2022). These tumors commonly present with metastasis and are resistant to conventional radioactive Iodine therapy and requires new systemic therapies focusing on the molecular profile of the tumors. Here we present a case of differentiated high grade follicular thyroid carcinoma in a 76-year-old female with distant metastases to the left 12th rib and L1 vertebral body.